Effect of Marxist ideological and political education on students’ anxiety in colleges and universities - Guo, Lingxia (Frontiers in Psychology, 2022)
With the rapid development of China's economy, politics, culture, society and ecological civilization, and the increasingly fierce social competition, the anxiety of college students has generally increased. The ideological and political educators in colleges and universities should help college students to relieve their anxiety and relieve their pressure in a timely manner, and constantly put forward effective and targeted methods. In this paper, questionnaires and in-depth interviews have been used to analyze the impact of mental health education courses on college students' anxiety management ability, and on this basis, suggestions have been put forward to play a positive role in mental health education courses in the development of college students' anxiety management ability. Among them, in the last class of the mental health education course, questionnaires were distributed to the selected research subjects. The state of their stress management abilities was known after taking the course. By analyzing and comparing the results of the two questionnaires before and after, as well as the conventional teaching methods of college students' mental health education and the teaching methods of group psychological counseling, it has been known whether there have been changes in the way college students deal with anxiety. The current situation of college students' anxiety has been analyzed from the aspects of how to deal with college students' interpersonal relationships, the degree of emphasis on college students' academic performance, and the ways of college students' self-decompression. Research has found that 19.23% of students have greater anxiety about interpersonal communication problems, and 9.62% of students have reported that they have no major anxiety problems. Therefore, Marxist ideological and political education in colleges and universities has become an important means for college students to vent their emotions, relieved psychological pressure, and avoided adverse consequences.